Efficient information-related practices in companies committed to EFQM. Issue 6 (10th October 2016) - Zárraga-Rodríguez, Marta; Álvarez, M. Jesús
Abstract : Purpose: The purpose of this paper is to explore whether or not companies committed to quality management within the European Foundation for Quality Management (EFQM) Excellence Model framework use and manage the information in an efficient way, i.e., they have developed information capability. In particular, this research investigates the links between information capability and the EFQM Excellence Model. Design/methodology/approach: This study is an extension of previous work by Zárraga-Rodríguez and Alvarez (2013), which was a first qualitative approach to the subject. In that work the EFQM Excellence Model criteria were analysed to see if somehow they illustrate practices associated to a company's information capability, self-analysis reports of a set of quality award winners were reviewed and interviews were conducted with members of those companies. The present research adopts a quantitative approach to gain deeper knowledge. Through a questionnaire survey the perceptions of managers in companies committed to the EFQM Excellence Model with respect to information capability-related practices and about the information they managed are captured. Findings: The analysis shows evidence that many information practices are common practices among companies committed to the EFQM Excellence Model and reveals information practices that should be improved. Originality/value: Practices that lead to efficient use and management of information have not been studied in detail in companies committed to quality management within the EFQM Excellence Model framework. Companies that are aware of the importance of handling quality information when making the decisions will find in this study a set of practices they can implement in order to achieve excellent performance based on the use and management of information.